1994
DOI: 10.1111/j.1365-2249.1994.tb06103.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of mannan-binding protein to various bacterial pathogens of meningitis

Abstract: SUMMARYMannan-binding protein (MBP), a calcium-dependent plasma lectin, may play a role in the innate defence against microorganisms. After binding lo carbohydrate structures at the bacterial surface, MBP activates the classical pathway of the complement system. To investigate the binding capacity of MBP to various bacteria associated with meningitis, an assay was developed to study the binding of MBP to bacteria grown in a semisynthctic lluid culture medium. Salmonella montevideo (containing a mannose-rich li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 32 publications
4
35
0
3
Order By: Relevance
“…2B and 2C). MBL did not bind to any bacteria tested, a finding consistent with previous observations (36,45). All strains to which L-ficolin/MASP complexes bound consumed C4 (Fig.…”
Section: Binding Of L-ficolin/masp and Mbl/masp Complexes To Intact Gsupporting
confidence: 91%
See 1 more Smart Citation
“…2B and 2C). MBL did not bind to any bacteria tested, a finding consistent with previous observations (36,45). All strains to which L-ficolin/MASP complexes bound consumed C4 (Fig.…”
Section: Binding Of L-ficolin/masp and Mbl/masp Complexes To Intact Gsupporting
confidence: 91%
“…One of these MASP, MASP-2, cleaves C4 and C2 to generate the C4b2a complex (40). Although it has been shown that L-ficolin binds to serotype III GBS CPS (3) and lipoteichoic acid (LTA) (29) and that MBL has low affinity for GBS (36,45), the studies were performed with restricted numbers of GBS strains. The ligand for both L-ficolin and MBL, N-acetylglucosamine (GlcNAc), is one of five monosaccharides incorporated into the CPS of GBS belonging to all serotypes (17-19, 21, 49-51) except serotype VI CPS (46) and serotype VIII CPS (20) and is a constituent of the group B-specific polysaccharide (GBPS) (33).…”
mentioning
confidence: 99%
“…The classical and lectin pathways display similar activation of C2, but our data indicate no activation by the lectin pathway of any importance, since similar results were obtained in MBL-sufficient and MBL-deficient individuals. This is in accordance with previously published results (7,21,46). These results are also in accordance with the well-established role of antibodies to effectively protect against meningococcal disease (14,16,20).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the wide array of infections reported in persons with MBL deficiency, several in vitro studies have demonstrated that MBL binds to a diverse spectrum of pathogens and that bound MBL can promote C4 deposition on the pathogen surface (116,181,226,231,318,465,481). Such studies have prompted investigators to link MBL deficiency with infections, and this is discussed next.…”
Section: Inherited Deficiencies Of Complement Activationmentioning
confidence: 67%